Factors Study of New Media Literacy in Indonesia on Environmental Awareness Character to Protecting The Environment - Putri, Kinkin Yuliaty; Sugiyatna, Lipur; Istiyanto, S Bekti (Unnes Science Education Journal, 2020)
The purpose of this research is to analyze new media literacy for the intelligence of society on Instagram regarding information on protecting the environment. The concepts used in this study are environmental communication, development communication, new media. The method used is quantitative research with analysis factors. Our respondets supported our research. The instrumen of validity and reliability are good. So we could continued to next factor analysis. Instagram as the object of research studies. Respondents of this study are commentators on Instagram's government in protecting the environment from October to December 2018. Conclusion our research is all dimension of literacy new media in Indonesia are positive. And suggestion of this research is that the community must be able to be given information on messages that can be immediately digested. Research impact is people must keeping how significant of content new media.